Presentation - Editors (Revista do Colóquio, 2021)
Under the title “Inhabitable worlds: images, bodies, places and discourses”, the twentieth issue of the Colloquium Journal brought a diverse set of works that discuss creative and research processes in different contexts, including reports of practical experiences and theoretical elucubrations.